Novel TLR7 hemizygous variant in post-COVID-19 neurological deterioration: a case report with literature review - Noor Eddin, Ahmed; Al-Rimawi, Mohammed; Peer-Zada, Feham; Hundallah, Khalid; Alhashem, Amal (Frontiers in Neurology, 2023)
The neurological complications of coronavirus disease 2019 (COVID-19) can range from simple tremors and dystonia to features of encephalopathy. Toll-like receptor 7 (TLR7) belongs to a family of innate immune receptors responsible for viral RNA detection (such as SARS-CoV-2) and immune response initiation. TLR7 loss of function variants have been previously reported as genetic risk factors for severe COVID-19 infection in young patients with no comorbidities. In this case, we report a pediatric patient who developed severe long-term neurological deterioration following his COVID-19 infection. Presenting first to the clinic with episodic dystonia and finger spasticity, the patient’s condition rapidly deteriorated with a significant drop in the Glasgow Coma Scale (GCS). Despite improvement following initial treatment with rituximab and intravenous immunoglobulin, the patient’s symptoms relapsed, and GCS further dropped to 3/15. Serial brain magnetic resonance imaging scans revealed diffuse parenchymal atrophy, ventricular enlargement, and spinal cord thickening. Autoimmune investigations were negative but clinical whole genome sequencing prioritized four gene variants, the most significant of which was a novel frameshift null variant of the X chromosomal TLR7 gene (c.1386_1389dup, p.[His464Ilefs*7]). This case illustrates a role for TLR7 in long-term COVID-19 complications and highlights that TLR7 deficiency in the future may be addressed as a therapeutic measure.